2022
DOI: 10.3390/jcm11040941
|View full text |Cite
|
Sign up to set email alerts
|

Association of Variability in the DDAH1, DDAH2, AGXT2 and PRMT1 Genes with Circulating ADMA Concentration in Human Whole Blood

Abstract: Asymmetric dimethylarginine is an endogenous inhibitor of nitric oxide synthesis and a cardiovascular risk factor. Its regulation has been studied extensively in experimental models, but less in humans. We studied common single-nucleotide polymorphisms (SNPs) in genes encoding for enzymes involved in ADMA biosynthesis and metabolism, i.e., PRMT1, DDAH1, DDAH2, and AGXT2, and assessed their associations with blood ADMA concentration in 377 unselected humans. The minor allele of DDAH1 SNP rs233112 was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In the present study, we aimed to evaluate the role of NO alterations in fetal programming of hypertension induced by maternal undernutrition during gestation, which we have previously demonstrated in adult male offspring [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34],…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we aimed to evaluate the role of NO alterations in fetal programming of hypertension induced by maternal undernutrition during gestation, which we have previously demonstrated in adult male offspring [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34],…”
Section: Discussionmentioning
confidence: 99%
“…ADMA and SDMA are released from tissues during physiological turnover of di-methylated proteins [21]. ADMA is enzymatically inactivated by dimethylarginine dimethylaminohydrolase (DDAH) [22] whilst SDMA is cleared by the kidneys. It was previously reported that dysfunction of the placental ADMA metabolism by DDAH contributes to high ADMA concentration in the late phase of pregnancy and may be one common cause of preeclampsia and FGR [2,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously analysed the associations of single nucleotide polymorphisms in genes encoding for major enzymes involved in the L-arginine/dimethylarginine/NO pathway with the circulating concentrations of L-arginine-related biomarkers. The major gene linked to ADMA plasma concentration is DDAH1, i.e., the gene encoding for one of two variants of the enzyme that converts ADMA to L-citrulline ( Leiper et al, 1999 ; Hannemann et al, 2022 ). SNPs in the DDAH2 gene are inversely associated with ADMA concentrations ( Hannemann et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The major gene linked to ADMA plasma concentration is DDAH1, i.e., the gene encoding for one of two variants of the enzyme that converts ADMA to L-citrulline ( Leiper et al, 1999 ; Hannemann et al, 2022 ). SNPs in the DDAH2 gene are inversely associated with ADMA concentrations ( Hannemann et al, 2022 ). By contrast, SNPs in the PRMT genes, which encode for a family of protein L-arginine methyltransferases that are involved in the formation of symmetrically or asymmetrically dimethylated L-arginine residues within proteins, have no associations with ADMA or SDMA concentrations ( Hannemann et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%